Rational solutions to Q3δ in the Adler-Bobenko-Suris list and degenerations. Issue 1 (2nd January 2019) - Zhao, Song-lin; Zhang, Da-jun
Abstract : We derive rational solutions in Casoratian form for the Nijhoff-Quispel-Capel (NQC) equation by using the lattice potential Korteweg-de Vries (lpKdV) equation and two Miura transformations between the lpKdV and the lattice potential modified KdV (lpmKdV) and the NQC equation. This allows us to present rational solutions for the whole Adler-Bobenko-Suris (ABS) list except Q4. The known Miura transformation for soliton solutions between the NQC equation and Q3δ and the known degenerations for solitons from Q3δ to Q2, Q1δ, H3δ, H2 and H1 in the ABS list are used. We show that the Miura transformation and degenerations are valid as well for rational solutions which are usually considered as "long-wave-limit" of solitons. All the rational solutions can be expressed in terms of {zj } which are linear functions of ( n, m ).